Rebranding: the road to competitiveness of small and medium businesses (2018)
The opening of new markets based on knowledge takes importance in the development of brands that are related to the lifestyle of the consumer. It is a challenge for the Pymes that have always underestimated their capacity to construct their own corporate identity. The aim of this paper is to analyze how through the repositioning of the brand, the enterprise competitiveness can be achieved no matter the size of the business, considering the constant investigation of the market. A descriptive study was developed in which three categories of analysis were defined: repositioning as a strategy, the construction of the brand and the competitiveness of Pymes. These categories were identified in 54 documents that correspond to scientific articles, books and thesis from academic databases. It is concluded that repositioning a brand demands the design and implementation of planning, communication and monitoring systems, in which all the areas of the organization participate in order to focus their economic and social activities in function of one or more markets.